SAHAM SEBAGAI INSTRUMEN DALAM KEBIJAKAN PASAR MODAL DI INDONESIA - Ridduwan, Muhammad; Hijawati, Hijawati; Yanuarsi, Susi; Husnulwati, Sri (Faculty of Law, University of Palembang, 2025)
This article is entitled the characteristics of shares as a capital market instrument in Indonesia. The problem studied in this article is how the characteristics of shares as a capital market instrument in Indonesia. The research method used in writing this article is the normative legal research method. The purpose of this study is to determine the characteristics of shares as a capital market instrument in Indonesia, while the benefits of this study are so that readers can determine the characteristics of shares as a capital market instrument in Indonesia. The findings of this study are that shares are a capital market instrument that has characteristics that are different from other securities. The differences in the characteristics of these shares are determined based on the classification of the shares themselves, namely the first common shares, namely shares that provide equal rights for each holder, the second preference shares, namely shares that have advantages in terms of dividend distribution and distribution of the Company's remaining assets from liquidation, and the third priority shares, namely shares that provide special rights to their holders. In addition, other differences are related to the issuance of shares in the capital market which must go through several stages, namely the pre-issuance stage, the issuance stage, and the post-issuance stage.